The phonological basis of Latin case patterns - Emonds Joseph Embley (Topics in Linguistics, 2014)
This study focuses on accounting for allomorphy in Latin case/number inflection. It attributes essentially all of it to the influence of adjacent features of standard segmental phonology on morphemes expressing case assignment. Indeed, other languages lead linguists to expect that allomorphy at a stem-suffix border can depend on any feature of a final vowel: ±Low, ±High, ±Round, ±Back, ±Consonantal or ±Syllabic. Empirically, it turns out that no two Latin stem-final vowels induce identical allomorphy in case/number suffixes, nor the same allomorphy as final consonants. Moreover, some (not much) phonologically conditioned allomorphy is phonetically opaque.